Role of the intermediary in implementation of the principles of sustainable development - O.O. Dyma (Marketing i Menedžment Innovacij, 2015)
The aim of the article. Worsening of environmental, social and economic problems require active role of business in solving them. One of the solutions of these problems is the implementation of principles of sustainable development in the practice of the state, business and consumers. Intermediaries should play a key role in this process, as they are an integral part of value creation network. Working in close relationship with producers and customers intermediary organizations can initiate the implementation of sustainable development not only at the macro but also at the micro level. The transition to the practice of sustainable development has a beneficial impact on the society and environment. Moreover, it can also have a positive effect on the intermediaries' financial performance. Adherence to the principles of sustainable development can help companies to achieve competitive advantages. The article is devoted to the peculiarities of sustainable development principles’ implementation by intermediary companies. A set of measures was developed to implement the principles of sustainable development. The results of the analysis. Lack of information is one of the main problems of sustainable development principles. Producers, customers and intermediaries do not have expertise in sustainable development principles’ implementation in the short and long-term perspective. To solve this problem the information system has been developed. The system allows the company to analyze the previous experience and share it with shareholders. The article highlights four groups of innovative activities aimed at achieving sustainable development objectives: activities to improve internal efficiency, new solutions in the field of organization of operations, optimization of product promotion activities as well as new forms of cooperation. Principles of sustainable development can be implemented via improvement of existing practices or completely new solutions. They can be adopted in internal or external environment of the intermediary. Sustainable development principles’ implementation and desired result can be achieved only by joint efforts of all participants of the value network. Sustainable development initiatives should be initiated by senior management and supported by other employees. Partners and competitors also play important role in this process. Potential employees, investors, partners and other stakeholders start paying more attention to the company’s initiatives in sustainable development principles’ realization. Sustainable development initiatives will not achieve the desired result without active and effective communications. Internal and external communication must strengthen the commitment of all parties to the idea of management, based on the principles of sustainable development. As it was stated above, the achievements of sustainable initiatives should be analyzed and shared among departments and partners. The study of the sustainable development experience of other parties, including competitors is also important. Conclusions and directions of further researches. Dissemination of information on sustainable development initiatives will not be enough to achieve positive results. It is important to organize coordination of efforts to implement the strategy of sustainable development. The role of company’s departments in realization of sustainable development initiatives has been defined. In addition, it is necessary to coordinate expansion of efforts to the entire value network to achieve the maximum cumulative effect in the current and future periods, because otherwise uncoordinated efforts can result in the reduction of overall efficiency.